Graphite Thin Films Production by Laser Ablation. - Riascos Landázuri, Henry; Marin, Juan Marcos; López Vargas, Juan David; Cuenca Vargas, Juan Pablo (Scientia et Technica, 2018)
Graphite thin films on silicon substrate were synthesized by the fundamental and second harmonics of a Nd : YAG pulsed laser, varying the substrate temperature from 200°C to 500°C . The oxygen gas pressure was of 2x10-5 Torr for all thin films grown. The samples were characterized by Raman and UV-Vis spectroscopy. With Raman spectroscopy the vibrational modes D, G and 2D, were identified. A strong dependence of the Absorbance of samples with substrate temperature was observed. The nanostructure of sample grown at 500°C corresponding to graphene oxide. The average thick of thin films was of 65 nm and 40 nm for fundamental and second harmonics respectively.